Enhancing teacher self-efficacy: The power of effective training programs - Tarik A. Alwerthan; Khulood M. Almajnuni (Journal of Pedagogical Research, 2024)
This study aimed to identify the relationship between training program effectiveness and English language teachers' self-efficacy. The participants of this study consisted of 144 English language teachers at Makkah schools. The data were collected via the Effectiveness of Training Program Scale and the Teachers Self-Efficacy Scale. The findings of the study revealed a statistically significant relationship between training programs effectiveness and English language teachers' self-efficacy. Furthermore, English teachers perceived self-efficacy toward student engagement and instructional strategies was medium, whereas classroom management was not high. Relevant implications and future directions are discussed within the scope of the training program effectiveness and teacher's self-efficacy literature.